Minority Stress Across the Career-Lifespan Trajectory. (April 2016) - Dispenza, Franco; Brown, Colton; Chastain, Taylor E.
Sexual minority persons (e.g., lesbian, gay, bisexual, and queer) are likely to encounter minority stress, such as discrimination, concealment, expectation of rejection, and internalized heterosexism. Minority stress occurs alongside one's lifespan and has considerable implications in the context of the career lifespan trajectory. Using the approach of developmental contextualism as a framework to embed minority stress, this article reviews the existing literature regarding facets of minority stress across the career lifespan trajectory and provides a conceptualization on how to incorporate minority stress into affirmative career appraisal, intervention, and research practices.